The Effect of Perceived Value on Customer Satisfaction and Customer Loyalty in the Fast-Food Industry in Indonesia - Gilang Pratama Hafidz; Khoerunisa Huriyahnuryi (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Customer Loyalty is an important factor that must be considered for every company, especially service providers. Maintaining customer loyalty is not easy for every company, because in this modern era many competitors are competing for customer loyalty. The purpose of this research was to explore the Influence of Perceived Value on Customer Satisfaction and Customer Loyalty. This type of research was quantitative using a purposive sampling technique which was distributed via a questionnaire to 240 fast food restaurant consumers aged 15-40 years in the JABODETABEK area. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study indicate that the eight proposed hypotheses are accepted, and the customer satisfaction variable has the greatest direct influence on corporate image. Then, Corporate Image has the greatest indirect effect on the relationship between Customer Satisfaction and Customer Loyalty. Researchers contributing to the company in maintaining and increasing customer loyalty can be seen from several aspects such as Perceived Value, Customer Satisfaction, Service Quality, and Corporate Image. For further research, the researcher suggests expanding the research area and looking for objects in other services.